Human Rights, vulnerability and pandemic - Dabove, María Isolina; D’Angelo, Eugenia; Hernández Bologna, Agostina Carla; Bariffi, Francisco; Schapiro, Hernán; Catanzaro Román, Mariana Guadalupe; Neira, Dolores (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2020)
This paper presents six dissertations on the problems faced by different vulnerable sectors of the population in the enjoyment of their human rights in the context of the global COVID-19 pandemic. The presentations reflect on the prejudices and vulnerabilities experienced by elderly adults; on gender-based violence during social isolation; on people in human mobility contexts who are excluded from protection measures; on the treatment and prioritization of people with disabilities in COVID-19 referral centres; on the protection of criminal safeguards in the administration of justice during the trials of crimes against humanity carried out remotely; and on the progress of the cases for crimes against humanity during the pandemic.
Keywords: human rights; pandemic; vulnerability; public policies; gender; elderly adults; gender violence; migrants; universality; disability; administration of justice; crimes against humanity